গনমাধ্যম ও সমাজ - মঞ্জু, কামরুল হাসান.; স্নিগ্ধা, জান্নাতুল ফেরদৌস.; Mass-Line Media Center (Dhaka, Bangladesh) (ঢাকা : মাস-লাইন মিডিয়া, 2002)
Contributed articles on social perspectives of mass media and adequacy of press coverage in Bangladesh; edited papers of various seminars.
In Bengali.
Keywords: Mass media -- Social aspects -- Bangladesh; Bangladesh -- Press coverage